Analysis of the Maintenance and Depreciation Costs and other Requirements of Selected Government Hospitals - Eduardo P. Banzon; Ma. Gerry Lyn Alcantara; Maria Alyanna Diez; Lorra Angelia Sayson (Philippine Institute for Development Studies (PIDS), 2014)
To a large extent, planning and budgeting in government hospitals are still carried out in an unsystematic, nonstrategic manner that goes against the thrust of current reforms. Historic budgeting proves to be inadequate in responding to the real needs of hospitals, especially in terms of maintaining its capital assets. The lack of clear guidelines and protocols on prioritization and budget decisions render the process vulnerable to subjective influences.This paper provides information on the appropriate capital management and investments in maintaining and upgrading equipment and capital plant by analyzing the budgeting practices, maintenance and depreciation costs, and requirements of public hospitals.
Keywords: 330; government hospitals; DOH-managed hospitals; LGU-managed hospitals; depreciation costs; maintenance and other operating expenses; capital assets; straight line depreciation; capital investment fund; output-based payments